Hydrogen fuel cells for road vehicles - Corbo, Pasquale; Migliardini, Fortunato; Veneri, Ottorino (London ; New York : Springer, 2011)
This book addresses the main issues related to the application of hydrogen fuel cell technology in the road transportation sector. Offers an introductory approach to fuel resources and atmospheric pollution concerns
1. Possible routes towards carbon-free vehicles -- 2. Hydrogen as future energy carrier -- 3. Fuel cells for automotive applications -- 4. Design of hydrogen cells systems for road vehicles -- 5. Electric vehicles in hybrid configuration -- 6. Case study A: fuel cell power train for mopeds -- 7. Case study B: fuel cell power train for cars
Includes bibliographical references and index
Keywords: Engineering; Fuel cell vehicles; Fuel cells